Implicazioni giuridiche dei “nuovi” fenomeni sociali: il Covid-19 (Società e diritti, 2020)
Abstract: The legal effectiveness and the evolution of law constitute mechanisms through which the law adopts tactics and strategies that allow it to reproduce and change: but they aren't the only tools through which law cognitively adapts to the environment and is able to learn. It is therefore necessary to analyze the mechanisms that allow the right to self-regulate on the basis of the legal implications of the “new social problems” connected to development, to the spread of the global pandemic from Covid-19.